UPAYA MENINGKATKAN HASIL BELAJAR IPA PADA MATERI GAYA MAGNET MELALUI MODEL INKUIRI TERBIMBING DI KELAS IV SDN RAWAMANGUN 02 PAGI - Zuhria Isnaini Latifah; Endang Wahyudiana; Ika Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Science lessons in grade IV at SDN Rawamangun 02 Pagi had previously been delivered through theoretical explanations, but there was still a lack of direct exploration activities, so many students had difficulty understanding the concept of magnetic force in concrete terms. As many as 65% of students had not achieved learning mastery due to the lack of simple experiments. By applying a guided inquiry model assisted by realia media, students were actively involved in experiments, such as testing objects around them to determine magnetic properties and observing magnetic pole interactions. The learning process was conducted in two cycles, including planning, action, observation, and reflection. Data collection techniques include tests, observations, field notes, and documentation. The results show an increase in learning mastery from 62% in Cycle I to 86% in Cycle II. The guided inquiry model assisted by realia media has proven effective in creating more active and concrete learning and improving science learning outcomes in elementary schools.